Ответы и объяснения

2012-12-12T11:05:13+00:00

2sin^2x+3cosx-3=0 
2(1-cos^2x)+3cosx-3=0 
2-2cos^2x+3cosx-3=0 
2cos^2x-3cosx+1=0 
Замена cosx=t, t [-1;1] 
2t^2-3t+1=0 
D=9-8=1 
t1,2=(3+-1)/4 
t1=1/2 
t2=1 
cosx=1/2 
x=+-pi/3+2pik, k Z 
cosx=1 
x=2pik, k Z 
Ответ: x=+-pi/3+2pik, k Z x=2pik, k Z

2012-12-12T11:29:26+00:00

1)

cos(1/2)=1  можетт cos(1/2*х)=1?

x/2 = 2*pi * n  

x = 4 * pi * n

n принадлежит Z

 

2)

cos2x = 2 * cos^2 x - 1

2*cos^2 x - 3 * cos x -1 = 0

особый случай а+в=с

cos x = - 1                     или           cos x =  1/2

x=рi * n                                             x = +- pi / 3 + 2 * pi * n

n принадлежит Z                                 n принадлежит Z

 

3)

sin(3x-pi/4) = 0

3x - pi/4 = pi * n

3x = pi * n + pi/4

x = (pi * n) / 3 + pi / 12

n принадлежит Z